2011
DOI: 10.1051/0004-6361/201016315
|View full text |Cite
|
Sign up to set email alerts
|

High-angular resolution observations of methanol in the infrared dark cloud core G11.11-0.12P1

Abstract: Recent studies suggest that infrared dark clouds (IRDCs) have the potential of harboring the earliest stages of massive star formation and indeed evidence for this is found toward distinct regions within them. We present a study with the Plateau de Bure Interferometer of a core in the archetypal filamentary IRDC G11.11-0.12 of a few arcsecond resolution to determine its physical and chemical structures. The data consist of continuum and line observations covering the C 34 S 2 → 1 line and the methanol 2 k → 1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
8
23
0
Order By: Relevance
“…1 , which is in agreement with " 10´1 0 from and on the lower end of observed values " 10´8´10´9 (Gómez et al 2011;Friberg et al 1988). Although, extraction of gas-phase abundances from observations remains challenging and needs to be approached cautiously.…”
Section: Chemical Evolutionsupporting
confidence: 69%
“…1 , which is in agreement with " 10´1 0 from and on the lower end of observed values " 10´8´10´9 (Gómez et al 2011;Friberg et al 1988). Although, extraction of gas-phase abundances from observations remains challenging and needs to be approached cautiously.…”
Section: Chemical Evolutionsupporting
confidence: 69%
“…An increase in the optical depth will decrease the density by roughly an order of magnitude for a given temperature and line ratio putting the range of densities for the clumps between 3 × 10 5 cm −3 to 3 × 10 6 cm −3 . These densities are consistent with earlier published results on N 2 H + in G28.34+0.06 (Chen et al 2010) and C 34 S in G11-MM (Gómez et al 2011). …”
Section: Column Density From Emission Linessupporting
confidence: 82%
“…On the basis of the observed correlation between the CH 3 OH and SiO abundances, SSH10 concluded that the origin of CH 3 OH in the MSX-dark clumps is related to shocks. Gómez et al (2011) inferred CH 3 OH abundances of ∼4 × 10 −9 −3 × 10 −8 in the IRDC core G11.11-0.12 P1, and also suggested that outflow desorption is responsible for the release of CH 3 OH from ice mantles. With comparable CH 3 OH abundances, this could also be the case in the MIR-dark clump SMM 3.…”
Section: Ch 3 Ohmentioning
confidence: 99%